Characteristics and applications of gas resources in abandoned coal seam groups within mining areas - Xuefeng TAO; Biming SHI; Jiwei YUE; Yuehui LIANG; Zhen ZHONG; Haiqing ZHANG; Wenqiang MEI; Yonglin XUE; Jie PENG; Chengcheng ZHANG (Meitan kexue jishu)
Affected by overcapacity, resource protection, international environment and other factors, the number of closed coal mines in Huainan and Huaibei areas is large, but the available resources of abandoned mines are rich and diverse. The secondary development and utilization of gas resources in abandoned mines is of practical significance to the current social development. Aiming at the problem of accurate prediction of gas resources in the development of gas resources in abandoned mines, by analyzing the reservoir space and content characteristics of gas in abandoned mines, it is proposed that the spatial distribution pattern of overlying strata caving cracks in adjacent upper and lower goafs is approximately two’ upper and lower series trapezoidal bodies '. Construct the concept of “solid before gas-dual source step by step” ( first, predict the remaining coal resources and recoverable coal reserves by level and block section; secondly, the evaluation model and method of gas resources in abandoned mines are predicted by using the coal resources of sub-level and sub-block sections combined with the gas content of coal seams. Using the established evaluation model and method, the remaining coal resources, recoverable coal reserves and gas resources of 13 minable coal seams in the abandoned mine of Panyi Coal Mine in Huainan were evaluated at different levels and blocks. The free gas resources in the goaf were calculated by using the theory of ‘new three zones’ of gas pressure relief and migration. The free gas resources in the goaf, caving zone and gas-conducting fracture zone of the working face in the goaf of 13–1 coal seam were calculated, and the gas in the lower part of the goaf was extracted by using the ground L-type test well. The research shows that the volume of the mined-out area connected by the upper and lower series trapezoidal bodies is larger than that of the unconnected mined-out area. The amount of remaining coal resources in the mine is 85 981×104 t, the amount of coal resources in the minable coal seam is 44 499×104 t, the amount of gas resources under the remaining coal resources is 42.690 334×108 m3, the amount of gas resources under the recoverable coal reserves is 22.397 501×108 m3, the amount of free gas resources in the goaf is 5 612.868 585×104 m3, and the total amount of extracted gas is 1 209.5×104 m3. The scale of gas resources in Panyi Mine is large, the gas resources are abundant, and the extraction effect is good, which provides a direction for the utilization of gas resources in abandoned mines.